Functioning of post-COVID-19 patients: a cross-sectional study at the outpatient clinic for long-term effects - Sanna Stålnacke; Helena Liira; Velina Vangelova-Korpinen; Hélène Virrantaus; Mari Kanerva; Kirsi Kvarnström; Markku Sainio; Antti Malmivaara; Aki Vuokko; Mikko Varonen; Mikko Venäläinen; Jari Arokoski (Taylor & Francis Group, 2024)
Background After COVID-19 infection, long-term impacts on functioning may occur. We studied the functioning of patients with post-COVID-19 condition (PCC) and compared them to controls without PCC.Methods This cross-sectional study consisted of 442 patients with PCC referred to rehabilitation at the Helsinki University Hospital (HUS) Outpatient Clinic for the Long-Term Effects of COVID-19, and 198 controls without PCC. Functioning was assessed with a questionnaire including WHODAS 2.0. Patients underwent physical testing including a hand grip strength test (HGST) and a 6-minute walking test (6MWT). Lifestyle was assessed by questionnaire and comorbidities were collected as ICD-10 codes from the HUS Data Lake on the HUS Acamedic platform.Results The WHODAS 2.0 average total score was 34 (SD 18) (moderate functional limitation) for patients with PCC and 6 (SD 8) (normal or mild limitation) for the controls. The disability was higher in all aspects of WHODAS 2.0 in patients with PCC. Bivariate binomial and multivariable regression analyses showed that the presence of comorbidities, anxiety, depression, and smoking predicted a WHODAS 2.0 score of 24 (moderate functional limitation) or above in the PCC group. The average 6MWT distance was 435 m (SD 98 m) in patients with PCC and 627 m (SD 70 m) in controls. HGST measurements showed no significant differences from controls.Conclusions In conclusion, patients with PCC had significantly reduced functioning based on WHODAS 2.0 scores and the 6MWT results. Comorbidities, anxiety, depression, and smoking were associated with moderate or severe limitations in functioning. Findings support that PCC is multifactorial and requires a holistic approach to rehabilitation.